HUMOR DALAM MAJALAH DJAKA LODANG (Kajian Bentuk Humor) - Mulyani, Siti (LITERA, 2005)
The use of puns to express humor in Djaka Lodang, a Javanese magazine, is a language phenomenon of language use that is interesting to study. This research study aims to (1) describe sections containing humorous discourses in Djaka Lodang, and (2) describe the forms of the humorous discourses. This study employed the descriptive approach. The data sources were Djaka Lodang published in the period of January to March 2003. The research data were segments of discourse containing humorous elements. The data were collected by reading and recording by means of the discourse analysis technique. The data validity was assessed through semantic validity. The data reliability was assessed by reading and rereading (intra-rater reliability). The data were analyzed by using the descriptive technique comprising induction and comparison, categorization, tabulation, and inference making. The research findings show that of 32 sections available in Djaka Lodang 18 sections contain humorous discourses. The 18 sections are (1) Cerita Rakyat, (2) Srumuwus, (3) Wawasan Droning Negara, (4) Wawasan Jaban Ranglcah, (5) Pagelaran, (6) Profil, (7) Sketsa, (8) Pedhalangan, (9) Lem bar Agama, (10) Macapat, (11) Seninjong, (12) Cerita Sambung, (13) Mendhowan, (14) Pengalamanku, (15) Cerita Cekak, (16) Wacan Bocah, (17) Tetepungan, and (18) Dhat Nyeng. There are seven forms of the humorous discourses, namely description, story, topic sentence, poem, magic spell, trapping expression, and pun.